Nonadiabatic quasiparticle description of rotation-particle coupling in triaxial odd–odd nuclei. (30th October 2020) - Siwach, Pooja; Arumugam, P; Modi, S; Ferreira, L S; Maglione, E
Abstract: A large wealth of data and a variety of models led to significant progress in understanding the spectra of deformed nuclei. However, a robust theoretical approach, which is less reliant on adjustable parameters is still elusive. Due to the scarcity of data, this drawback gets more pronounced while studying the exotic nuclei. With the motive to overcome this difficulty, we have developed the nonadiabatic quasiparticle approach for the description of rotational states in triaxial deformed odd–odd nuclei. The rotation-particle coupling is carried out utilizing an appropriate basis transformation such that the matrix elements of the odd–odd system can be written in terms of the rotor energies. This provides the advantage of studying the role of core more efficiently as compared to the conventional particle rotor model. The residual interaction between the valence proton and neutron is incorporated in two reliable ways, namely, the constant potential form and the zero-range interaction.